(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article scientifically analyzes the role of individual characteristics in the formation of the athlete’s personality. Health as an invaluable asset of every person is one of the important conditions for the socio-economic development of society. It has been argued that sport and physical education play an important role in promoting a healthy lifestyle